If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(3x + -13) = 10 Reorder the terms: 5(-13 + 3x) = 10 (-13 * 5 + 3x * 5) = 10 (-65 + 15x) = 10 Solving -65 + 15x = 10 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '65' to each side of the equation. -65 + 65 + 15x = 10 + 65 Combine like terms: -65 + 65 = 0 0 + 15x = 10 + 65 15x = 10 + 65 Combine like terms: 10 + 65 = 75 15x = 75 Divide each side by '15'. x = 5 Simplifying x = 5
| 3b^2=21b | | 5x^2+4x-20=0 | | 3(y-5)+2(3+y)=21 | | 12-x=-(x+12) | | 7x+17=101 | | 7x-21=42 | | .333(18x-12)=2(3x-2) | | 117-(-60)= | | 25x-5=3x+6 | | .5(x+4)=2+.5x | | x+8=x+12 | | 2e^4x-11=0 | | 2(2-3x)=-6(x+2) | | 2(e^4x-3)=8 | | 11+5=5+47 | | 6x-19=4y | | t=cm | | 7(x-2)=4(2x+1) | | 8y-6=5y | | a^2+2ab+b^2=y | | 6-x=x+6 | | 3x-5=3x+7 | | a^2+2ab+b^2=64 | | 4(x-3)+8=40 | | x(4+2)=84 | | 6x+19=4y | | 2(2X+5)=10 | | -5x-8y=24 | | 227=x | | 10-5y=1-y | | 2y-7.2+y=9.6 | | y=0.4(x-2)(x-13) |